PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN DAERAH PROVINSI KEPULAUAN RIAU - Jupriadi J; Rahman Hasibuan; Ferry Muliadi Manalu (BENING, 2015)
Developments in science and technology are rapidly bringing fundamental change in human life to improve the performance of the individual and society. Human resource issues to internal problems within an organization. Performance of employees is very important and is the end result of the accumulation of all the process there are various factors that influence employee performance. Such as leadership and job satisfaction. This study will focus on the Department of Revenue Riau Islands Province. Sampling technique using census techniques, because the relatively small population of 30 people, type of data used is primary data. Data collected through the distribution of questionnaires. Once it is done with the method of testing the validity and reliability of the instrument. The data analysis technique used is descriptive analysis. Based on the analysis and discussion in the previous famil, it can be concluded as follows: (1) Respondents' perceptions about leadership is good, perserpsi respondents about job satisfaction is high and the perception of respondents about the employee's performance is very high. (2) There is a positive and significant effect between leadership on employee performance. (3) The existence of a positive and significant effect between job satisfaction on employee performance. (4) The existence of a positive and significant effect between leadership and job satisfaction on employee performance. As for suggestions that could be addressed in this study include: (1) Should the company can improve the leadership has been good, this can be done by paying attention to subordinates. (2) Receipt Party can maintain job satisfaction of employees who have been included in the category are satisfied. (3) In the next study may add other variables that influence employee performance such as: stress of work, commitment and communication.